Evaluasi Efektivitas Program Bridging Penulisan Dasar Ilmiah bagi Mahasiswa Kerja Sama Pemerintah Kabupaten Puncak - Ivona Dorobia; Selmina Rumawak; Onisimus Faot; Paskalis Kaipman; Demmy Tabuni (Bajang Institute, 2026)
This study aimed to evaluate the effectiveness of the Scientific Academic Writing Bridging Program for students participating in the partnership between the Government of Puncak Regency and Universitas Internasional Papua in improving their academic writing skills prior to entering regular university courses. The study employed a mixed-methods approach with a sequential explanatory design. The participants consisted of 28 students enrolled in the Bridging Program. Quantitative data were collected through pre-test and post-test scores, while qualitative data were obtained from classroom observations, documentation, reflective notes, and students' writing portfolios. Data were analyzed using descriptive statistics, Normalized Gain (N-Gain), comparative tests based on data distribution, and thematic analysis. The findings revealed that the students' mean score increased from 38.86 in the pre-test to 62.96 in the post-test, indicating that the Bridging Program effectively improved their basic academic writing skills. Qualitative findings also demonstrated improvements in idea development, text organization, and the use of academic language. The program's success was supported by structured instruction, continuous writing practice, constructive lecturer feedback, and active student participation. Overall, the Bridging Program serves as an effective strategy for strengthening the academic readiness of students from Indonesia's disadvantaged, frontier, and outermost (3T) regions before entering higher education.